Platelet Function Inhibitors in the Year 2000 - Bennett, Joel S.; Mousa, Shaker (Thrombosis and Haemostasis, 2001)
Platelet thrombi are responsible for much of the morbidity and mortality of arterial vascular disease (1). Because platelet inhibitors such as aspirin have proven to be of benefit to patients with these disorders, there has been a directed search for more potent anti-platelet agents. The following discussion addresses the mechanism of action and clinical utility of the currently available platelet function inhibitors. Although in theory these agents could impair platelet adhesion, aggregation, secretion, or platelet procoagulant activity, in practice they are focused almost exclusively on the biochemical events that proceed from platelet stimulation to ligand binding to the platelet fibrinogen receptor GPIIb-IIIa.
Keywords: Arterial thrombosis; platelet inhibitors; GPIIb-IIIa; aspirin; thienopyridines